Pengaruh Citra Merek Dan Mutu Produk Terhadap Keputusan Pembelian Buds Organics - Erwin Rasyid; Rani Apriani (UniSadhuGuna Business School, 2022)
This study aims to examine the effect of Brand Image and Product Quality on Buds Organics Purchase Decisions at PT Inti Berkat Jaya. Accidental sampling was chosen as the sampling technique because it has a benchmark: Baby Empire customers who use buds are 76 respondents. The analysis technique chosen is quantitative analysis and multiple linear regression requiring simultaneous F-test and partial t-test. And the results show that the selected 2 independent variables (brand image and product quality) simultaneously have a significant and significant effect on purchasing decisions with a significance of 0.000 < 0.05. And the R Square value obtained in this study is 0.597, meaning that 59.7% of Purchase Decisions can be explained by brand image and product quality and the remaining 40.3% (100% - 59.7% = 40.3%) explained by other variables that were not examined. Then for the results of the partial study, the independent variables consisting of Brand Image and product quality are positive and significant.